Effect of Spirulina and Probiotic on Growth Performance of Japanese Quail - alhussaini, Ruaa; Bahaa A. Alsereah; Assad H. Eissa (University of Thi-Qar Journal of agricultural research, 2023)
The aim of current project is to fortify the quail feeds with various types of supplements such as spirulina, Used as a substitute for Prob. & study the growth performance to recognize the best formula of spirulina for best production. untreated was feed on standard diet, Spirulina group was feed with Spirulina , Probiotics complex group was feed with probiotics complex, Mix Spirulina with probiotic complex group was feed with above Spirulina & probiotic. complex. BW, BWG, FI & FCE were daily recoded. Results noted at highest significant increase (P≤0.05) for the addition of spirulina occurred in the average body weight of Japanese quail compared to the control and other treated groups. The highest significant increase (P≤0.05) occurred in the BWG rates of birds treated with the addition of spirulina for weeks (1 and 4) and the cumulative (1-6) weeks. the highest rate (p≤0.05) of feed consumption was recorded in the group of birds treated with spirulina for weeks (2, 3, 4, 5, and 6). and the cumulative feed consumption rate from (1-6) weeks compared with the other treatments and the control group. Rresults showed FCE rates recorded a significant improvement in adding spirulina during (1,2,3,4,6) weeks and the cumulative feed conversion efficiency average (1-6) weeks for birds. From this research, we concluded that adding spirulina to quail diets improved productive traits.